Lactose intolerance but not lactose maldigestion is more frequent in patients with irritable bowel syndrome than in healthy controls: A meta‐analysis. Issue 5 (17th December 2018) - Varjú, Péter; Gede, Noémi; Szakács, Zsolt; Hegyi, Péter; Cazacu, Irina Mihaela; Pécsi, Dániel; Fábián, Anna; Szepes, Zoltán; Vincze, Áron; Tenk, Judit; Balaskó, Márta; Rumbus, Zoltán; et al.
Abstract: Background and Purpose: Irritable bowel syndrome (IBS) affects 10%‐20% of the adult population and is characterized by abdominal symptoms without relevant organic disease. There are numerous clinical trials available investigating the relationship between IBS, lactose maldigestion (LM), and lactose intolerance (LI), but there have been no meta‐analyses on this topic yet. We aimed to assess the prevalence of LM, objective and subjective (self‐reported) LI in IBS patients compared to healthy controls (HC) without IBS. Methods: A systematic literature search was conducted up to 24 April 2018 in PubMed, Embase, and Cochrane Library. Adult IBS patients had to be diagnosed according to the Rome criteria or other well‐defined criteria system. We enrolled controlled studies including healthy adult participants without IBS, as control group. Odds ratios with 95% confidence intervals were calculated. Key Results: Altogether 14 articles were suitable for statistical analyses. IBS patients reported themselves significantly more frequently lactose intolerant than HCs (odds ratio [OR] = 3.499; 95% confidence interval [CI] = 1.622‐7.551). Generally, there was no significant difference in the prevalence of LM based on ingested lactose dose (OR = 1.122; 95% CI = 0.929‐1.356) and test type (OR = 1.156; 95% CI = 0.985‐1.356). However, significantly more IBS patients had objective LI (OR = 2.521; 95% CI = 1.280‐4.965). Conclusions and Inferences: Lactose intolerance, but not LM is more frequent among patients with IBS compared to HCs. According to our results, IBS among other functional bowel disorders is a possible contributing factor of LI in people with LM. Abstract : Irritable bowel syndrome (IBS) affects 10%‐20% of the adult population and is characterized by abdominal symptoms without relevant organic disease. There are numerous clinical trials but not meta‐analysis available investigating the relationship between IBS, lactose maldigestion (LM), and lactose intolerance (LI). LI, but not LM is more frequent among patients with IBS compared to healthy controls. According to our results, irritable bowel syndrome among other functional bowel disorders is a possible contributing factor of lactose intolerance in people with lactose maldigestion.